2010
DOI: 10.1111/j.1600-0854.2009.01028.x
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the Definition of the Classical Bipartite Nuclear Localization Signal

Abstract: Nuclear localization signals (NLSs) are amino acid sequences that target cargo proteins into the nucleus. Rigorous characterization of NLS motifs is essential to understanding and predicting pathways for nuclear import. The best-characterized NLS is the classical NLS (cNLS), which is recognized by the cNLS receptor, importin-α. cNLSs are conventionally defined as having one (monopartite) or two clusters of basic amino acids separated by a 9-12 aa linker (bipartite). Motivated by the finding that Ty1 integrase,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
110
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(117 citation statements)
references
References 60 publications
(96 reference statements)
6
110
0
Order By: Relevance
“…8D), which makes a distance of 1-2 aa for the spatial distance between the two basic clusters that interact with the minor binding site and major binding site in importin-a, respectively. A previous report also showed that Ty1 integrase contains a bona fide bipartite NLS with a 29-aa linker (37). Our data, together with these reports, reveal that the traditional definition of NLS is too restrictive; the linker length can vary depending on amino acid composition and conformation.…”
Section: Discussionsupporting
confidence: 77%
“…8D), which makes a distance of 1-2 aa for the spatial distance between the two basic clusters that interact with the minor binding site and major binding site in importin-a, respectively. A previous report also showed that Ty1 integrase contains a bona fide bipartite NLS with a 29-aa linker (37). Our data, together with these reports, reveal that the traditional definition of NLS is too restrictive; the linker length can vary depending on amino acid composition and conformation.…”
Section: Discussionsupporting
confidence: 77%
“…The intervening sequence between the two basic rich sequences in a bipartite NLS is generally 10-12 amino acids long. In the cofilin NLS, this intervening sequence is shorter than predicted, however, it has been reported that the number of amino acids between the basic regions of a bipartite NLS can vary greatly, being either longer (Lange et al, 2010) or shorter (Taniguchi et al, 2002) than the earlier defined consensus. When we mutated both basic regions of the bipartite NLS (AASSTPEEVKAAKK) the nuclear localization signal was not functional, either out of context or in context of full length cofilin.…”
Section: Discussionmentioning
confidence: 85%
“…The solid-phase binding assay was performed essentially as described previously (Matsuura et al, 2003;Lange et al, 2010;Takeda et al, 2011;Marfori et al, 2012). The assay was performed on Immuno MaxiSorp 96-well plate (Thermo Fisher Scientific).…”
Section: Microtiter Plate Binding Assaymentioning
confidence: 99%